Keanekaragaman Bivalvia dan Gastropoda di Pulau Nangka Kabupaten Bangka Tengah - Alita Alita; Henri Henri; Rahmad Lingga; Anna Sonia; Gita Fitri; Stevani Greacela Putri; Arinda Salsabila (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2021)
This study aims to determine the type and level of diversity of Bivalves and Gastropods found on Nangka Island, Tanjung Pura Village, Central Bangka Regency, Bangka Belitung Islands Province. The method used in this research is purposive sampling with a line transect technique, which is carried out by taking a determined line in a direction perpendicular to the shoreline and consists of 3 sampling plots made of a quadrant frame measuring 1×1 m2 with a total sampling area of 81. The results showed that the physical and chemical parameters of the environment at the observation site were classified as good with an average temperature of 32°C, total dissolved solids (TDS) of 2,069.1 ppm, turbidity of 0.08 NTU, and a water pH of around 7.767. The diversity of Gastropods is greater than the diversity of Bivalves. This is indicated by the presence of 17 species of Gastropods and 5 species of Bivalves. The most common species found at the study site was Cerithium scabridum with a total of 581 individuals. The most commonly found family from the Gastropods class is the Muricidae family, while the Bivalves class is the Veneridae family. Environmental parameters measured at the study site such as temperature, total dissolved solids (TDS), turbidity, and water pH indicated that the environmental conditions supported the life of Bivalves and Gastropods as indicated by the high abundance and diversity of shellfish and snails.